(untitled) (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2024)
This study aims to evaluate the use of the role play method in teaching speaking skills to tenth-grade students at Satria Mandiri Private Vocational School. This method involves students in role-playing situations that simulate everyday conversations in English. The research findings indicate that students engaged in role play showed a significant improvement in their speaking abilities compared to the control group. This suggests that the use of the role play teaching method can effectively enhance students’ speaking skills. The data were analyzed using the Kolmogorov-Smirnov normality test, with a significance value of Sig. > 0.05, indicating a normal distribution of the research data. The homogeneity test results showed a significance value of 0.101 > 0.05, indicating that the data were distributed normally and homogeneously. The paired sample t-test, based on pre-test and post-test data from the experimental group, yielded a two-tailed significance value of 0.005 < 0.05, indicating a significant improvement in students’ speaking abilities after implementing the role play method. The average pre-test score for the experimental group was 88, increasing to 91 in the post-test. The experimental group showed a greater improvement compared to the control group, whose average pre-test score was 58, increasing to 60 in the post-test. This suggests that the use of the role play method has an impact on the speaking abilities of tenth-grade students. As a result, the alternative hypothesis (Ha) is accepted, while the null hypothesis (Ho) is rejected, indicating the effectiveness of the role play method in enhancing students’ speaking skills. This study contributes significantly to understanding the effectiveness of role play teaching methods in the context of speaking instruction, particularly in vocational high school environments